2022
DOI: 10.2147/bctt.s353332
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Treatment-Induced Bone Loss: Role of Denosumab in Non-Metastatic Breast Cancer

Abstract: Chemotherapeutic agents, endocrine therapy and radiotherapy used in the management of breast cancer are known to cause decreased bone mineral density, and thus, increased incidence of fractures. A majority (~60%) of the breast cancer patients in India are either estrogen (ER) or progesterone hormone receptor (PR) positive. Adjuvant treatment with aromatase inhibitors (AIs) is the treatment mainstay for hormone-sensitive disease in postmenopausal (PM) women, with reduced bone mineral density (BMD), which result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
(96 reference statements)
0
3
0
1
Order By: Relevance
“…However, it is still controversial whether these genes are associated with BMD. The results of a prospective cohort study showed that VDR CC genotype and COLIA1 TT genotype were associated with increased hip fracture risk in Caucasian women, and this association was independent of BMD and age ( 110 ). ER gene are not associated with osteoporotic fractures, bone mass, or bone turnover ( 111 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is still controversial whether these genes are associated with BMD. The results of a prospective cohort study showed that VDR CC genotype and COLIA1 TT genotype were associated with increased hip fracture risk in Caucasian women, and this association was independent of BMD and age ( 110 ). ER gene are not associated with osteoporotic fractures, bone mass, or bone turnover ( 111 ).…”
Section: Resultsmentioning
confidence: 99%
“…Solo il Dmab 60 mg/ogni 6 mesi ha dati di efficacia sulla riduzione delle fratture nelle donne con CM trattate con inibitori dell'aromatasi e negli uomini con CP in blocco androgenico [45,46] . In una network to mantenuto per i 3 anni di follow-up [40] .…”
Section: Ctibl E Suo Managementunclassified
“…Breast cancer surgery may result in tissue necrosis and scarring at the operated site reducing spine, chest, shoulder girdle, and upper limb mobility, weakening the torso and upper limb muscles, and disturbing biomechanical and postural control [ 7 ]. Radiotherapy and hormonal therapy can precipitate menopause and cause hormonal imbalance contributing to bone mass reduction [ 8 , 9 ]. Immunotherapy is indicated to be associated with the inflammatory diseases of internal organs, chronic fatigue, and sometimes with adverse changes in the central nervous system [ 10 ].…”
Section: Introductionmentioning
confidence: 99%